PENGARUH PENEMPATAN KERJA TERHADAP DISIPLIN KERJA PEGAWAI STUDI PADA PDAM TIRTA INTAN KABUPATEN GARUT - Tommy Indra Gunawan; Ai Ropikoh (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This research has a background where the work discipline of PDAM Tirta Intan Garut Regency employees is still not optimal in carrying out their work activities. This phenomenon can be caused by various factors, including the work placement factor. The purpose of this study was to determine the effect of work placement on employee work discipline at PDAM Tirta Intan, Garut Regency. The method used in this research is descriptive and associative. Quantitative data in this study were obtained through a questionnaire. Based on the analysis and data, information was obtained that the research instruments used in this study were declared valid and reliable because they had a value greater than the r table of 0.202. From the results of the partial correlation test, work placement has a positive and significant effect on employee work discipline where the level of influence lies in a strong position with an r value of 0.698 and a coefficient of determination of 52.5% and the remaining 47.5% is influenced by other factors that not examined such as compensation, motivation, leadership and others. While the respondents' responses regarding work placement at PDAM Tirta Intan Garut Regency were in the good category and for employee work discipline at PDAM Tirta Intan Garut Regency in the good category.